Long-Run Monetary and Fiscal Policy Trade-Off in an Endogenous Growth Model with Transaction Costs - P. Villieu; Alexandru Minea (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2007)
In this paper, we study maximizing long-run economic growth trade-off in monetary and fiscal policies in an endogenous growth model with transaction costs. We show that both monetary and fiscal policies are subject to threshold effects, a result that gives account of a number of recent empirical findings. Furthermore, the model shows that, to finance public expenditures, maximizing-growth government must choose relatively high seigniorage (respectively income taxation), if ?tax evasion? and ?financial repression? coefficients are high (respectively low). Thus, our model may explain why some governments resort to seigniorage and inflationary finance, and others rather resort to high tax-rate, as result of maximizing-growth strategies in different structural environments (notably concerning tax evasion and financial repression). In addition, the model allows examining how the optimal mix of government finance changes in response to different public debt contexts.
Keywords: H6; E5; E6; O4; 330; endogenous growth; threshold effects; monetary policy; fiscal policy; public deficit; policy mix; tax evasion; financial repression